HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN TINGKAT DEPRESI PADA LANSIA DI KELURAHAN SADING - Gusti Ayu Trisna Parasari; Made Diah Lestari (Jurnal Psikologi Udayana, 2015)
Elderly are age group that susceptible to depression. Depression in elderly is caused by lack of ability to adapt to changes in self as result of physical, mental and social decline. Severity of elderly depressive disorders are categorized into three levels, namely no depression, mild depression and moderate/severe depression. Family social support plays an important role in helping the elderly in adapting to the changes that occur in order to reduce the level of depression. This quantitative research with correlation approach aims to determine the relationship between family social support with level of depression in elderly in Sading Village. The samples cosisted of 233 elderly in Sading Village were taken using simple random sampling technique. This study uses two scales of measurement namely the family social support scale and the level of depression scale (Geriatric Depression Scale) adapted from Yesavage et al. (in Azizah, 2011). Family social support scale consists of 33 items with the reliability value = 0,968 and level of depression scale consists of 30 items with the reliability value = 0,948. The analysis technique used in this study is the Spearman Rank correlation. The analysis result showed that there was a significant relationship between family social support with level of depression (p = 0,000, p <0,05). The correlation r = -0.847 can be concluded that family social support has a opposite direction relationship with level of depression. This means that the higher family social support received, then the level of depression in elderly in Sading Village would be lower. Keywords: Family Social Support, Level coefficient of Depression and Elderly